Creating opportunities for occupational development using the concerns report method. (3rd September 2018) - Leclair, Leanne; Ali, Sophia; Finlayson, Marcia
Abstract: Background: Little research has focused on working with communities to promote and support children's occupational development. Aim/Objective: We used the Concerns Report Method (CRM) to identify community supports for parents with young children that could enhance children's occupational development. Material and method: We conducted interviews/focus groups with parents ( n = 29) and service providers ( n = 11). We used content analysis to identify four themes: availability, barriers and facilitators, parent/child transitions, and making connections. The themes were used to create a concerns report survey for parents and service providers. A random sample of parents ( n = 319) and convenience sample of service providers ( n = 47) in one community area of a Canadian urban center completed the on-line survey. We held a community forum to review the results and identify solutions for action. Results: Parents' highest priorities included childcare, supports in community schools, preschool programs, and supports in one location. Service providers highest priorities included: identification of developmental concerns; parenting education; programs for fathers, programs that offer child care, a doctor, and child care. Conclusions: Service providers need to engage parents and consider parents' perspectives when planning services to ensure community supports will meet parent identified needs. Significance: Using community-based participatory research approaches, occupational therapists can contribute to children's occupational development.